Enhancing Deradicalization Preaching Through Literacy and Technology: A Training and Media Approach - Khoiri Khoiri; Anis Farihah (Indonesian Journal of Cultural and Community Development, 2023)
This scientific article presents an innovative approach to strengthening deradicalization efforts, focusing on the role of Da'i Agents of Peace empowered by Muhammadiyah. The study's objectives encompass the cultivation of three key deradicalization programs: nurturing individual development, fostering self-reliance, and providing sustained preventive guidance. Addressing the dearth of qualified preachers adept in classical interpretive and hadith literature, the research underscores the urgency of enhancing human resources capabilities. The intervention revolves around two primary initiatives: immersive workshops elucidating polar fathul at tafsir and technology-driven hadith comprehension, alongside facilitation in crafting technology-based da'wah content. This article highlights the outcomes of these initiatives, emphasizing amplified literacy skills and heightened understanding of hadith interpretations as pivotal achievements. The implications extend to the enrichment of deradicalization strategies and the broader potential for technology-enhanced religious outreach. Highlight: Innovative Approach: This article introduces a novel method for enhancing deradicalization efforts, focusing on the pivotal role of Da'i Agents of Peace under Muhammadiyah's empowerment. Multi-Faceted Objectives: The study aims to nurture personal development, foster self-reliance, and provide continuous preventive guidance as integral components of deradicalization programs. Human Resources Enhancement: The research underscores the pressing need to bolster the capabilities of preachers in classical interpretive and hadith literature, advocating for improved human resources strategies. Keyword: Deradicalization, Da'i Agents of Peace, Muhammadiyah, Technology-driven Da'wah, Literacy Enhancement